Cameroon Social Safety Nets - del Ninno, Carlo (World Bank, Washington, DC, 2014)
This report lays the groundwork for a safety net system that can address the needs of the poor in Cameroon. Cameroon does not have a coordinated system of safety nets; rather, small, isolated interventions which together do not address the needs. Moreover, food and fuel price subsidies which mainly benefit the rich cost around 2 percent of GDP/year much more than total safety net spending. There is a need for a social protection strategy and an effective safety net system to address chronic poverty and food insecurity in Cameroon. This strategy should identify risks and vulnerabilities so they can be addressed by appropriate programs. Investments in human capital and in geographic areas most affected by poverty the North and Far North should be priority.